Cognitive Principles in the Basis of Default Metonymy - Milkevich Elena Stepanovna (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2016)
The article studies metonymy in English. Traditionally metonymy is understood as a stylistic device. This, however, does not explain the cases of everyday or ‘default’ metonymy, such as ‘to go to the blackboard’ (in the meaning of answering the home task), or ‘to sit behind the wheel’ (in the meaning of ‘driving). Cognitive view on metonymy speaks about metonymic relationships between concepts within idealized cognitive models. The choice of metonymic vehicle and desired target can be governed by cognitive principles based on human experience, selective perception and cultural awareness.